KASUS RECURRENT PAINFUL OPTHTHALMOPLEGIC NEUROPATHY : KONDISI YANG JARANG DITEMUKAN: (CASE OF RECURRENT PAINFUL OPTHTHALMOPLEGIC NEUROPATHY : A RARE CONDITION) - Whisnu Nalendra Tama; Fahreza Hanifa Akbar; Indra Sari Kusuma Harahap; Desin Pambudi Sejahtera; Sekplin Sekeon; Yudiyanta (Neurologi Manado, 2020)
Recurrent Painful Opthalmoplegic Neuropathy (RPON), formerly called opthalmoplegic migraine, has been described as recurrent attacks of headache followed by ophthalmoplegia. This is a rare condition and its pathophysiology is still under debate. Many authors report the use steroid as the main therapy, although its effectiveness is only found in a few cases. Steroid-non-responsive condition is a challenge in the management of RPON especially related to headache and perceived diplopia. This case report described a patient diagnosed with RPON and its management complexity. Keywords: Recurrent Painful Opththalmoplegic Neuropathy